Never change a winning team: An analysis of hazard rates in the NBA - Alexander Dilger (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2002)
We estimate Cox models to determine proportional hazard rates in professional basketball, concerning leaving the league or changing the team by using a database covering all players of the NBA in the 90's. We predict and confirm that league-hazards depend on a player's performance. A teamswitch, however, cannot depend on low performance itself because there has to be a team willing to accept the (new) player. Accordingly we find that a good scoring performance and an intense use of a player reduces the probability of a team-switch, whereas high salaries or non-scoring performance do not.
Keywords: 330; Professioneller Sport; Sportökonomik; Gruppenarbeit; Arbeitsmobilität; Mikroökonometrie; Schätzung; USA